(untitled) (Revista Internacional de Formação de Professores, 2022)
This paper presents the results of a documental study in the realm of history about both implementation and itinerary of the Externato Normal (high school teachers’ courses), from 1886-1892 in North-Parahyba Province. The creation of this institution was one of the first steps taken by local public government, in order to normatize teaching education and practice, with a view to instructional activities in primary schools. The documental body used was composed of: speeches and reports by presidents of the Paraiban Province, as well as public teaching managers’ reports, addressed to Provincial presidents, Laws and Regulations of public teaching, besides local newspapers production of that time. Such an investigation has produced an amount of aspects related to teachers’ training, and its process of institutionalization in Paraiban society, during the second half of the XIX century. Thus, it contributes to new challenges and knowledge increase of Brazilian educational history, specifically of progression and regression in teachers’ education.